(untitled) - Spencer, Herbert (London, 1903)
The growing demand for the original edition of these chapters on Education has suggested to me the propriety of issuing an edition that shall come within easy reach of a larger public: what knowledge is of most worth, intellectual education, moral education, physical education.
Keywords: Education,Giáo dục